Accreditation and quality assurance in vocational and educational training : selected European approaches - (:unkn) unknown (Publications Office of the European Union, 2009)
"Accreditation is the mechanism for external assessment of VET providers, certifying their compliance with predefined objectives, criteria and standards. In this respect, accreditation encourages conformity rather than, ideally, improvement. Quality is considered a modernisation factor for VET systems. Quality assurance renders the system accountable for effectiveness, also promoting common understanding and trust. Accreditation is testified by a certificate/label with marketing value as it positions its holder within the steadily expanding VET market. There are currently many labels and certificates. The present Cedefop publication aims at shedding light on some issues common to accreditation approaches in VET within the EU." (Herausgeber, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 2.2.4.3 Zertifizierung; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2 Europa; Berufsbildung; Zertifizierung; Qualitätssicherung; Evaluation; Europa